Problems of Tourism Leakage in Badung Regency due to Foreign Tourist Invasion - Margayawati, Ni Luh Putu; Dewi, Nyoman Diah Utari; Widnyani, Ida Ayu Putu Sri (Goodwood Publishing, 2025)
Purpose: Bali Province, a popular tourist destination, is facing challenges due to the